Management of an Ailing Anterior Implant Using a Minimally Invasive Flapless Surgical Technique: A Case Report. Issue 4 (1st November 2017) - Constantinides, Christos; Chang, Jaime; Fletcher, Paul
Abstract : Introduction: Peri‐implantitis is an inflammation of the soft and hard tissues surrounding an implant that results in the destruction of alveolar bone. Surgical flaps are usually elevated to allow for thorough debridement and disinfection of the implant surface. This frequently results in gingival recession, crown margin exposure, and a poor esthetic result. This is not desirable in the esthetic zone. In this case report, a minimally invasive flapless technique incorporating the use of curettage and antiseptics is used to successfully disinfect a contaminated dental implant to allow for soft tissue readherence and pocket reduction. Radiographic bone fill is also seen. The results have been maintained for 2 years. Case Presentation: A 54‐year‐old female patient presented with peri‐implantitis, characterized by episodic pain and suppuration from a buccal fistula on an implant replacing tooth #10. The implant was placed and provisionally restored 10 years previously. It showed radiographic bone loss to the fifth thread, but it was non‐mobile. Treatment consisted of removal of the temporary crown and abutment, which provided access for the surgical curettage of the granulomatous tissue and for the mechanical debridement of the implant surface with a titanium curet. Chemical detoxification of the implant surface, as well as the abutment, screw, and screw hole, was achieved with the use of sterile saline and a 0.25% sodium hypochlorite solution. Antibiotics were also prescribed. At a 2‐year follow‐up, probing depths were reduced to <4 mm, and there was radiographic bone fill. Conclusions: A minimally invasive flapless technique incorporating surgical curettage debridement of the inflamed soft tissue and chemical detoxification with antiseptics can be a viable alternative for the treatment of anterior implants with peri‐implantitis, especially when the patient has a high smile line. Successful and effective debridement and disinfection of a previously contaminated implant surface can be achieved without reflecting a flap.